How to predict peak front crawl swimming performance? - Toussaint, H.; Truijens, M. (Japanese Journal of Sciences in Swimming and Water Exercise, 2004)
Peak performances in sport require the full deployment of all powers an athlete possesses. How factors like mechanical power output, technique, and drag each on itself, but also in concert determine swimming performance is subject of inquiry. This overview of swimming biomechanics focuses on three performance factors: (i) generation of propulsion in water, (ii) drag encountered by the body during swimming and (iii) propulsive efficiency. The theoretical considerations will be put to use by predicting individual power requirements for swimming a world record in the 50 m free style based on experimental data.